Sulfonated SnO2nanocatalysts: Via a self-propagating combustion method for esterification of palm fatty acid distillate - Nabihah-Fauzi, N. (Royal Society of Chemistry, 2020)
Biodiesel derived from palm fatty acid distillate (PFAD) was produced via catalytic esterification using sulfonated tin oxide (HSO3-/SnO2) as the superacid solid catalyst. In this work, the SnO2 catalyst was synthesised by the self-propagating combustion (SPC) method, and activated using chlorosulfonic acid. The SPC method was able to produce nano-sized particles with homogenous size and shape that were anchored with many HSO3- ions, resulting in more exceptional acid properties that effectively esterified the PFAD feedstock into FAMEs (fatty acid methyl esters). Several studies based on metal oxide-based catalysts were also included for comparison. Under the optimised conditions of 9â:â1 (methanol-to-PFAD molar ratio), 4 wt (catalyst loading), 100 Â°C (reaction temperature) and 3 h (reaction time), the FFA conversion and FAME yield were 98.9 and 93.8, respectively. Besides, the sulfonated SnO2-spc catalyst can be reused in up to five consecutive cycles with an acceptable esterification performance and minimal sulfur leaching. It is worth mentioning that the SPC method is a greener and simpler technique to obtain the nanocatalysts. Overall, the production of FAME from low value, cheaper, abundant, and non-edible PFAD feedstock, assisted by a non-transition metal oxide of sulfonated SnO2 catalyst, could reduce the cost of biodiesel production. This journal is Â© The Royal Society of Chemistry.